Physician incentives in managed care organizations: Medical practice norms and the quality of care - David J. Cooper; James B. Rebitzer (Levy Economics Institute of Bard College, 2002)
This brief considers the interaction between physician incentive systems and product market competition in the delivery of medical services via managed care organizations. At the center of the analysis is the process by which health maintenance organizations (HMOs) assemble physician networks and the role these networks play in the competition for customers. The authors find that although physician practice styles respond to financial incentives, there is little evidence that HMO cost-containment incentives cause a discernable reduction in care quality. They propose a model of the managed care marketplace that solves for both physician incentive contracts and HMO product market strategies in an environment of extreme information asymmetry: physicians perceive the quality of care they offer perfectly and their patients do not perceive it at all.
Keywords: 330; Managed Care; Ärzte; Leistungsanreiz; Krankenversicherung; Dienstleistungsqualität; Wettbewerb; USA